2019
DOI: 10.3389/fcell.2019.00341
|View full text |Cite
|
Sign up to set email alerts
|

Signaling Enzymes Required for Sperm Maturation and Fertilization in Mammals

Abstract: In mammals, motility and fertilizing ability of spermatozoa develop during their passage through the epididymis. After ejaculation, sperm undergo capacitation and hyperactivation in the female reproductive tract-a motility transition that is required for sperm penetration of the egg. Both epididymal initiation of sperm motility and hyperactivation are essential for male fertility. Motility initiation in the epididymis and sperm hyperactivation involve changes in metabolism, cAMP (cyclic adenosine monophosphate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 145 publications
1
40
0
Order By: Relevance
“…Among the changes occurring within the female genital tract (i.e. capacitation), were described alkalinization of the cytoplasm, membrane hyperpolarization and protein phosphorylation cascades induced by the activation of soluble adenylate cyclase (sAC) and protein kinase A (PKA), which specifically target flagellar components required for sperm fertilization potential 16 …”
Section: Introductionmentioning
confidence: 99%
“…Among the changes occurring within the female genital tract (i.e. capacitation), were described alkalinization of the cytoplasm, membrane hyperpolarization and protein phosphorylation cascades induced by the activation of soluble adenylate cyclase (sAC) and protein kinase A (PKA), which specifically target flagellar components required for sperm fertilization potential 16 …”
Section: Introductionmentioning
confidence: 99%
“…Spermatozoa require several enzymes and receptors for their movement. 32 The results of this study showed that the administration of ethanolic S. betaceum extracts significantly affected the total motility of spermatozoa. The highest percentage increase in the mean total motility is shown by giving the highest dose of 400 mg/kg body weight.…”
Section: Discussionmentioning
confidence: 70%
“…In addition to the integrity of the fibrous sheath, sperm motility also depends directly on cAMP and calcium functioning. cAMP has been reported as an essential element in the initiation of sperm motility, as it can activate tyrosine kinase and increase the flagellar beat frequency [ 24 ]. Past studies have thoroughly investigated the role of calcium in sperm motility, indicating that increasing Ca 2+ concentration can raise the sperm glycolysis level and promote motility hyperactivation [ 25 ].…”
Section: Discussionmentioning
confidence: 99%